Surgico-Therapeutic Management of Supracondylar Fractures in Felines using Arrow-Pin Technique - Saini , Dishant; Khandekar, Gajendra S; Tripathi, S D; Gaikwad, S V; Chauhan, Shalaka A; Patil, Harshal (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The “Arrow pin technique” is a modified version of using intramedullary pins to mend femoral diaphyseal/ metaphyseal (supracondylar)  fractures. The arrow pins were “custom made” by cutting locally available stainless-steel rod into predetermined lengths pins, further  flattening one end, creating groves on either side of the flattened end with a file to give the appearance of an arrowhead, and shaping  the opposite end as a trocar point. The pin insertion was accomplished aseptically through lateral approach on the distal femur, through  the trochlear groove under general anaesthesia in cats. The clinical efficacy of this arrow pin technique was evaluated in six cats. All  the cats (n=6) were client owned and < 1-year-old, with supracondylar distal femoral fractures. Following the clinical and radiological  examinations, the type and location of the fracture, details of the fixation method applied, postoperative clinical and radiological results  were assessed. After radiographic evaluation, long bone fractures were classified as supracondylar fractures of type I overridden closed  fractures. Following the insertion of an intramedullary arrow pin, robust stability was accomplished, as evidenced radiographically.  The patients were able to bear weight on the affected limb in 3-5 days and began walking normally on day 14 after surgery. The study  found that the single “custom made” arrow pins provided adequate stability and resistance to rotational and axial forces in distal femoral  fractures, and it confirmed that it would provide a significant fracture reduction in long bone fractures in young cats at a low cost.
Keywords: Arrow-pin; Fracture healing; Feline; Intramedullary pinning; Supracondylar